Quercetin ameliorates chicken quality by activating the PI3K/PKB/AMPK signaling pathway in broilers - Wang, Mi; Wang, Bo; Zhou, Shuaishuai; Liu, Jiayan; Lu, Han; Wu, Hao; Ding, Manyi; Li, Yao (Frontiers in Veterinary Science, 2022)
This study was conducted to investigate the effects and mechanism of quercetin on chicken quality in broilers. We selected 480 AA broilers (1 day old) and randomly allotted those to four treatments (negative control and 0.2, 0.4, or 0.6 g of quercetin per kg of diet) for 42 days. Compared with the control group, the supplementation with 0.4 g of quercetin significantly increased the pH45min and L* value of the thigh muscle and decreased the shearing force of the thigh muscle and breast muscle and drip loss of the thigh muscle (P < 0.05). The supplementation with 0.6 g/kg of quercetin significantly increased the pH45min and L* value of the thigh muscle, and pH45min of breast muscle and decreased the drip loss of the thigh muscle (P < 0.05). Sensory scores of meat color, tenderness, and juiciness also were improved with increasing quercetin concentration (P < 0.05). The inosinic acid (IMP) content of the breast and thigh muscles of broilers was significantly increased by supplementation with 0.6 g/kg of quercetin (P < 0.05). Supplementation with 0.2, 0.4, and 0.6 g of quercetin significantly reduced mRNA expression of L-FABP (P < 0.05, P < 0.05, and P < 0.05); supplementation with 0.4 and 0.6 g/kg of quercetin significantly increased mRNA expression of PKB and AMPKα1 (P < 0.05 and P < 0.05); supplementation with 0.6 g/kg of quercetin in the diet significantly reduced mRNA expression of SREBP1 and HMGR (P < 0.05 and P < 0.05) and significantly increased mRNA expression of CPT1 and PPARγ (P < 0.05 and P < 0.05); and supplementation with 0.2, 0.4, and 0.6 g/kg of quercetin significantly increased mRNA expression of PI3K, LPL, and Apo A1 and significantly reduced mRNA expression of ACC and FATP1 in the breast muscle of broilers (P > 0.05). PI3k, PKB, AMPK, SREBP1, and L-FABP were significantly and positively correlated with pH45min (P < 0.05); PPARγ was significantly and positively correlated with shear force (P < 0.05); CPT1 was significantly and positively correlated with the L* value (P < 0.05); and HMGR was significantly and positively correlated with drip loss (P < 0.05). In conclusion, quercetin improved the meat quality, protecting it against lipid oxidation and deposition by regulating the PI3K/PKB/AMPKα1 signaling pathway in the breast muscle of broilers.